RI 4350 Investigation Of The Blewett Zinc-Lead Deposit - Jo Daviess County, Ill. - Stephen P. Holt (The National Institute for Occupational Safety and Health (NIOSH), 1948)
During the spring and summer of 1946, the Bureau of Mines put down 8 churn-drill holes and 9 diamond-drill holes, totaling 3,535 feet of bore, at the Blewett zinc-lead deposit in Jo Daviess County, Ill. Attention of the Bureau of Mines was first directed to this deposit by the Illinois State Geological Survey, which had investigated the Blewett mine. In the opinion of the Survey and the Bureau of Mines, the record of production and results of drilling previously done on the property were considered sufficient justification for continuing investigation to the north and south along a projection of the trend. This report describes the work done by the Bureau on this, property and presents the data obtained.